Agricultural Information Needs of Rainfed Farmers: A Study from Telangana - CN, Anshida Beevi; Nirmala, G; Rohit, Jagriti; Nagasree, K; Raju, B M K (Journal of Extension Education, 2020)
A paradigm shift in rainfed agriculture can be obtained mainly through technological interventions. In this context, the role of extension and advisory services that are saddled with this responsibility should focus on novel approaches. Application of relevant information in agriculture sector brings positive impacts on farm productivity. Timely access to information on weather aspects, best farming practices, market information etc. help farmers to make correct decisions about what crops to plant, when to plant and where to sell their products. The best way to satisfy the rainfed farmers is to understand and consider their specific needs, constraints and capabilities properly, which helps to serve them in an efficient manner. A study has been undertaken to understand the different agricultural information needs of rainfed farmers in the Mahabubnagar district of Telangana state India. It is observed that farmers need various types of information related to agricultural activities and the major agricultural information needs of the farmers were found to be related to farm implements and machinery, water management, seed varieties, seed treatment, alternate crops and pest and disease management. In order to address these information needs, farmers were accessing a number of sources. It is important to enhance the information search capacity of the rainfed farmers to improve the farm productivity and income leading to enhanced livelihoods.